Learn to listen and give voice to children - Mesquita, Cristina (2011)
The focus of the study lies in the development of a praxis that claims that the child as an individual with competence and rights to participate. It relates to EEL Project (Pascal & Bertram, 1999) and to DQP (Oliveira-Formosinho, 2002, 2009), which supports the present study, by enhancing the development of children, practitioners and institutions. This study focuses on a professional development theory that links the action to the context, sustaining an ecological perspective (Bronfenbrenner, 1987). The study locates itself in the qualitative paradigm (Denzin & Lincoln, 2000) an is conducted through a constractivistic case study (Oliveira-Formosinho & Kishimoto, 2002). Data is collected before and after the change processes and impact is evaluated through some of the EEL techniques